Matrix metalloproteinase activity during methamphetamine cued relapse. (13th April 2023) - Lewandowski, Stacia I.; Hodebourg, Ritchy; Wood, Samuel K.; Carter, Jordan S.; Nelson, Katherine H.; Kalivas, Peter W.; Reichel, Carmela M.
Abstract: Relapse to drug seeking involves transient synaptic remodelling that occurs in response to drug‐associated cues. This remodelling includes activation of matrix metalloproteinases (MMPs) to initiate catalytic signalling in the extracellular matrix in the nucleus accumbens core (NAcore). We hypothesized that MMP activity would be increased in the NAcore during cue‐induced methamphetamine (meth) seeking in a rat model of meth use and relapse. Male and female rats had indwelling jugular catheters and bilateral intracranial cannula targeting the NAcore surgically implanted. Following recovery, rats underwent meth or saline self‐administration (6 h/day for 15 days) in which active lever responding was paired with a light + tone stimulus complex, followed by home cage abstinence. Testing occurred after 7 or 30 days of abstinence. On test day, rats were microinjected with a fluorescein isothiocyanate (FITC)‐quenched gelatin substrate that fluoresces following cleavage by MMP‐2, 9, allowing for the quantification of gelatinase activity during cued‐relapse testing. MMP‐2, 9 activity was significantly increased in the NAcore by meth cues presentation after 7 and 30 days of abstinence, indicating that remodelling by MMPs occurs during presentation of meth associated cues. Surprisingly, although cue‐induced seeking increased between Days 7 and 30, MMP‐2, 9 activity did not increase. These findings indicate that although MMP activation is elicited during meth cue‐induced seeking, MMP activation did not parallel the meth seeking that occurs during extended drug abstinence. Abstract : Drug‐induced synaptic remodelling of the extracellular matrix by matrix metalloproteinases occurs in the nucleus accumbens core during drug seeking. Here, we show that MMPs are activated during relapse to meth‐associated cues during early and late abstinence in male and female rats.